ACG Clinical Guidelines: Management of Benign Anorectal Disorders. (October 2021) - Wald, Arnold; Bharucha, Adil E.; Limketkai, Berkeley; Malcolm, Allison; Remes-Troche, Jose M.; Whitehead, William E.; Zutshi, Massarat
Abstract : Benign anorectal disorders of structure and function are common in clinical practice. These guidelines summarize the preferred approach to the evaluation and management of defecation disorders, proctalgia syndromes, hemorrhoids, anal fissures, and fecal incontinence in adults and represent the official practice recommendations of the American College of Gastroenterology. The scientific evidence for these guidelines was assessed using the Grading of Recommendations Assessment, Development and Evaluation process. When the evidence was not appropriate for Grading of Recommendations Assessment, Development and Evaluation, we used expert consensus to develop key concept statements. These guidelines should be considered as preferred but are not the only approaches to these conditions.